The silent spread: exploring diverse metastatic pathways in high-grade serous ovarian cancer - Mengqi Deng; Mengqi Deng; Ruiye Yang; Ruiye Yang; Junyi Jiang; Jinxu Zhang; Junqi He; Junqi He; Jinwei Miao; Jinwei Miao (Frontiers in Medicine)
High-grade serous ovarian cancer (HGSOC) is a highly aggressive and deadly gynecological cancer, with metastasis being a key factor in its poor prognosis. Historically, HGSOC was thought to spread primarily through the peritoneal cavity, but recent research has revealed additional routes of metastasis, including the blood and lymphatic systems. This review discusses the complex processes of HGSOC metastasis, focusing on peritoneal immune suppression, stromal reprogramming, and the role of circulating tumor cells in blood-based spread. We also explore the clinical significance of lymphatic metastasis, particularly its impact on patient outcomes. Gaining insight into molecular and genetic drivers, such as BRCA mutations and interactions within the immune microenvironment, is essential for developing targeted treatments. Future studies should aim to enhance experimental models, identify early detection markers, and investigate novel therapeutic approaches to effectively address HGSOC metastasis and improve patient survival.